2021
DOI: 10.1055/a-1493-5627
|View full text |Cite
|
Sign up to set email alerts
|

Dilation-predominant approach versus routine care in patients with difficult-to-treat eosinophilic esophagitis: a retrospective comparison

Abstract: Background & Aims: Little is known about esophageal dilation as a long-term treatment eosinophilic esophagitis (EoE). We examined the impact of a “dilate and wait” strategy on symptoms and safety of patients with EoE. Methods: This retrospective cohort study included two groups of EoE patients: those who underwent a dilation-predominant approach, defined as >3 dilations as EoE sole therapy or for histologically refractory disease (>15 eos/hpf); and those who had routine care, defined as <3 dilati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Further supportive evidence for the role of strictures, rather than inflammatory activity, in generating symptoms includes the positive initial symptomatic response from dilation in patients where eosinophilic inflammation is left unchecked. 5,6 The findings of Safroneeva et al 1 are therefore supportive of the postulate that fibrostenotic luminal narrowing resultant from untreated eosinophilic inflammation, rather than the inflammation itself, is the predominant driver of symptoms in a proportion of patients with eosinophilic esophagitis. Although this is yet to be conclusively established, further research into the relationship between fibrostenosis (both endoscopically apparent and inapparent), dilation, and symptom burden in eosinophilic esophagitis will be invaluable, and has potential to change the treatment paradigm by expanding the role of dilation in these patients.…”
Section: Underrecognized Fibrostenotic Luminal Narrowing May Explain ...mentioning
confidence: 92%
“…Further supportive evidence for the role of strictures, rather than inflammatory activity, in generating symptoms includes the positive initial symptomatic response from dilation in patients where eosinophilic inflammation is left unchecked. 5,6 The findings of Safroneeva et al 1 are therefore supportive of the postulate that fibrostenotic luminal narrowing resultant from untreated eosinophilic inflammation, rather than the inflammation itself, is the predominant driver of symptoms in a proportion of patients with eosinophilic esophagitis. Although this is yet to be conclusively established, further research into the relationship between fibrostenosis (both endoscopically apparent and inapparent), dilation, and symptom burden in eosinophilic esophagitis will be invaluable, and has potential to change the treatment paradigm by expanding the role of dilation in these patients.…”
Section: Underrecognized Fibrostenotic Luminal Narrowing May Explain ...mentioning
confidence: 92%
“…A dilationpredominant long-term treatment strategy can be considered for symptom control in patients with a persistently symptomatic refractory stricture or as a temporizing measure at the initial or continued implementation of medical therapy. [95][96][97][98] 11. The immediate endpoint of endoscopic dilation is the appearance of a mucosal disruption or reaching the target diameter.…”
Section: Endoscopic Gradingmentioning
confidence: 99%
“…However, multiple studies have addressed technique, target diameter, and overall outcome. [95][96][97][98] Potential factors that contribute to dilation success in EoE include predilation stricture diameter, location and extent of the fibrostenotic disease, presence of inflammation or fragility of the tissue, when moderate resistance is encountered during dilation, presence of blood on a dilator, and/ or visualization of mucosal disruption. The bougie method allows for tactile feedback so the endoscopist may gauge when initial and moderate resistance is encountered as an endpoint.…”
Section: Endoscopic Gradingmentioning
confidence: 99%
See 1 more Smart Citation
“…A systematic review and meta-analysis found 95% clinical improvement with dilation and low rates (<1%) of major complications [8]. Dilation is an option for managing fibrostenotic disease and can provide symptomatic relief for 15–17 months regardless of medical therapy [9,40 ▪ ,41]. Work from the Northwestern group in a group of patients with severe strictures (oesophageal lumen <10 mm) managed with serial dilations found that 89.4% of patients experienced improvement in oesophageal diameter to at least 13 mm and 65.2% to at least 15 mm.…”
Section: What Are Other Treatment Options For Patients With Refractor...mentioning
confidence: 99%